PENERAPAN WHISTLEBLOWING SYSTEM TERHADAP INTERNAL FRAUD PADA PT. BANK MUAMALAT INDONESIA, TBK PERIODE 2015-2019 - Gina Sakinah; Ade Ponirah (LIKUID: Jurnal Ekonomi Industri Halal, 2021)
Banks or other financial industries are particularly vulnerable to internal fraud cases. This is motivated because the highest motivation of this action is a financial factor. Every bank has now tried as early as possible to prevent the occurrence of internal fraud by using whistleblowing system that is part of internal control to realize good corporate governance, this system is useful to disclose violations that occur in the company by accommodating information from whistleblowers either from employees or from other stakehlolder by maintaining the confidentiality of identity and information. This study was conducted at PT. Bank Muamalat Indonesia, Tbk. by using descriptive method of quantifiable by presenting numerical data obtained from GCG report. The results of the analysis showed there is still a high level of internal fraud from 2015 to 2016 the highest cases that are in 2016 fluctuating until 2019. This indicates that the whistleblowing system implemented has not been optimal. Employees still do not have a sense of deterrent effect if they commit such actions, and the banking system that is less efficient and low supervision from internal and external parties becomes a great opportunity to commit crimes.Keywords: Whistleblowing System, Internal Fraud